Criminal Law Analysis of Discriminatory Content and Digital Radicalization on Online Platforms - Assaad, Istiqlal (Jurnal Hukum dan Keadilan, 2025)
Digital platforms have become primary spaces for information dissemination while simultaneously facilitating the spread of discriminatory content and radicalization narratives that may threaten social order and national security. Within Indonesia’s criminal law framework, the regulation of such phenomena remains problematic due to normative ambiguity, particularly in distinguishing the boundaries between freedom of expression, discriminatory speech, and radicalizing content. This study aims to analyze the regulation and application of criminal law concerning discriminatory and radical content on digital platforms and to examine the implications of normative ambiguity for legal certainty and human rights protection. Employing a normative juridical method with statutory, conceptual, and case approaches, the study finds that unclear definitions and regulatory overlap among the ITE Law, the Law on the Elimination of Racial and Ethnic Discrimination, and the Anti-Terrorism Law result in inconsistent law enforcement and the risk of over-criminalization. The study concludes that clearer and more harmonized criminal norms are essential to ensure legal certainty, effective enforcement, and the protection of human rights in the digital sphere.